Assessing Quality of Life in Long-Term Survivors after 125I Brachytherapy for Low-Grade Glioma in Childhood - Korinthenberg, R.; Neuburger, D.; Nikkhah, G.; Teske, C.; Schnabel, K.; Calaminus, G. (Neuropediatrics, 2011)
Quality of life (QOL) is important for the survivors of malignancies. We investigated health-related QOL in 51 patients treated with iodine-125 (125I) brachytherapy for childhood low-grade gliomas. Instruments included a questionnaire on life situation, German versions of PEDQOL (8−18 years), EORTC QLQ-30 and head and neck module H&N-35 (>18 years), strength and difficulties questionnaire, “Fertigkeitsskala Münster Heidelberg”, and an adapted Rankin score. The time lapsed since 125I-brachytherapy was 134 months (median, range: 29−293 months). 57% of the patients were over 18 years of age, 34% were 11−17 years old and 8% were younger. 14 had undergone other treatments after 125I brachytherapy. Over half of the >18 year olds reported residual problems; 68% were disabled, 38% to a severe degree. Many of the young adults still lived with their parents and 17% were jobless. 43% of the children/adolescents needed rehabilitative treatment, 20% visited special schools and 71% were disabled, 33% severely. The patients and their caregivers rated their QOL as not different from that of the normal population. However, many QOL dimensions correlated to the severity of disability. Comparison of QOL outcomes between different treatment measures would require a prospective study controlling for the most important factors of influence.
Keywords: children; glioma; iodine-125 brachytherapy; quality of life; long-term follow-up